Impact of achievement of complete cytogenetic response on outcome in patients with myelodysplastic syndromes treated with hypomethylating agents. Issue 4 (13th February 2017) - Jabbour, Elias; Strati, Paolo; Cabrero, Monica; O'Brien, Susan; Ravandi, Farhad; Bueso‐Ramos, Carlos; Wei, Qiao; Hu, Jianhua; Abi Aad, Simon; Short, Nicholas J.; Dinardo, Courtney; Daver, Naval; et al.
Abstract: Two hundred and sixteen consecutive patients with MDS and abnormal karyotype treated with hypomethylating agents between 4/04 and 10/12 were reviewed. Median follow‐up was 17 months. Using IWG criteria, best responses were complete response (CR) in 79 patients (37%), partial response (PR) in 4 (2%), and hematologic improvement (HI) in 10 (5%). Cytogenetic response (CyR) was achieved in 78 patients (36%): complete (CCyR) in 62 (29%) and partial in 16 (7%). CyR was achieved in 48 of 79 patients (61%) with CR, 1 of 14 (7%) with PR/HI, and in 29 of the 123 (24%) with no morphologic response. Median overall survival (OS) and leukemia‐free survival (LFS) for patients with and without CCyR were 21 and 13 months ( P = .007), and 16 and 9 months ( P = .001), respectively. By multivariate analysis, the achievement of CCyR was predictive for better OS (HR = 2.1; P < .001). In conclusion, CyR occurs at a rate of 36% (complete in 29%) in patients with MDS treated with HMA and is not always associated with morphological response. The achievement of CCyR is associated with survival improvement and constitutes a major predictive factor for outcome particularly in patients without morphologic response. Therefore, the achievement of CCyR should be considered a milestone in the management of patients with MDS.